Choices and Chances in Programs and Plans for the Gaining of Credentials: Perspectives From A Small Rural High School - Franklin, Janice (Australian and International Journal of Rural Education, 2010)
Research about rural education, and education policy directions for rural schools, are set against formal measures of 'disadvantage'. These measures about rural 'disadvantage' have been defined, evaluated and compared to more 'advantaged' provincial and urban schools. Rarely has educational research or policy been 'inverted' to be defined, evaluated and prescribed from within the rural, to focus on education for rural young people. This paper tests the validity of the historic and contemporary emphasis about disadvantage in rural and remote education. It evaluates the ways staff and students prepared for student transition from school to employment or further education in one small rural high school. The school of the study is situated in a community which has all accepted measures of economic and social disadvantages including isolation and low socio-economic status. Prolonged drought, and government intervention to replace native timber harvesting with national parks in state forest areas, and the expansion of softwood plantations on farmland, together have restricted employment in the these locally restructured timber and farming activities. The school's plan and programs designed to prepare students for their transition to employment and further education, acknowledge that the high school, the community it serves, and its students, are 'disadvantaged' in all measures. Key school documents, as these described the school's programs, activities and endeavours and staff interviews produce a view from 'above'. This was compared to the view of the Year 11 school cohort who had been invited to participate in two Focus Group Interviews, and a From School to Further Education or Work Survey. Their view from 'below' indicated a significant disconnection between the school staff and the students about what values and experiences most influence student decisions about school completion, and their chances of achieving their chosen transition goals. The study revealed that the focus on 'disadvantage', as this underpinned the school's plans and practices for student transition, called into question the relevance of the programs that were designed to redress educational 'disadvantage.